Próba zastosowania metod statystycznych w analizie skłonności homoseksualnych - Obidzińska, Olga; Obidziński, Piotr (Trial of statistical methods applications in homosexual inclination analysis, 2006)
The purpose of article is trial of statistical estimate influence of traumatic infancy experience on create homosexual inclination. In addition author presents the measures of own opinion level and tendency to depression level. Analysis concern on male homosexuality. There was three groups of men receive to the research: homosexual gay, homosexual not a gay and the third heterosexual to comparison.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (13); 2006; nr 1126, s. 465-474